1979
DOI: 10.1007/bf01420205
|View full text |Cite
|
Sign up to set email alerts
|

Applications of functional analysis to the solution of power series equations

Abstract: In the study of local rings arising in algebraic geometry one often puts a topology on these rings -the Krull topology, in which a neighborhood base of 0 consists of all powers of the maximal ideal. The Krull topology plays an important role in the study of many topics which appear to be purely algebraic rather than topological. The most basic tools for the study and application of the Krull topology are probably the Artin-Rees lemma, which asserts that if R is a local Noetherian ring and N, M are finitely gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In fact, by [4] and [30], (ii) is equivalent to the regularity of 0 at a. (i) Ker H^ is generated by Ker Y^ .…”
Section: Invariants Of Gabrielovmentioning
confidence: 99%
“…In fact, by [4] and [30], (ii) is equivalent to the regularity of 0 at a. (i) Ker H^ is generated by Ker Y^ .…”
Section: Invariants Of Gabrielovmentioning
confidence: 99%
“…where m is the maximal ideal of S. By the rank of (p we mean the rank of The proof of all the unnumbered implications has already been given in [9] or theorem 2.1.…”
Section: Q(s/r)=d(s/r)/n Mwr) 1=1mentioning
confidence: 99%
“…In [9] we continued the investigation of the properties of local algebra homomorphisms begun in [2,12,14,18], and showed that if (p : R -> S is an algebra homomorphism of reduced analytic rings over C which is closed in the Krull topology, then (p is open in the Krull topology. This can be restated as follows : If (p is injective and cp(R) n S = (p(R), then (p : R -> S is injective, where hat denotes completion.…”
Section: Solving Power Series Equations Part II : Change Of Ground Fmentioning
confidence: 99%
See 2 more Smart Citations